2022
DOI: 10.3389/fbioe.2022.916605
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Saccharomyces cerevisiae for Heterologous Carnosic Acid Production

Abstract: Carnosic acid (CA), a phenolic tricyclic diterpene, has many biological effects, including anti-inflammatory, anticancer, antiobesity, and antidiabetic activities. In this study, an efficient biosynthetic pathway was constructed to produce CA in Saccharomyces cerevisiae. First, the CA precursor miltiradiene was synthesized, after which the CA production strain was constructed by integrating the genes encoding cytochrome P450 enzymes (P450s) and cytochrome P450 reductase (CPR) SmCPR. The CA titer was further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Despite the cells suspension of L. meyenii represents a good system to evaluate diverse elicitors and precursors involved in CA and CS biosynthesis, the production of other compounds should be further addressed. Recent studies based on metabolic engineering have been reported recombinant yeasts able to produce 76 mg L −1 under bioreactor conditions [35] . Nevertheless, only traces of CS (which also shows a wide spectrum biological activities) were detected in this system.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite the cells suspension of L. meyenii represents a good system to evaluate diverse elicitors and precursors involved in CA and CS biosynthesis, the production of other compounds should be further addressed. Recent studies based on metabolic engineering have been reported recombinant yeasts able to produce 76 mg L −1 under bioreactor conditions [35] . Nevertheless, only traces of CS (which also shows a wide spectrum biological activities) were detected in this system.…”
Section: Resultsmentioning
confidence: 86%
“…Recent studies based on metabolic engineering have been reported recombinant yeasts able to produce 76 mg L À 1 under bioreactor conditions. [35] Nevertheless, only traces of CS (which also shows a wide spectrum biological activities) were detected in this system. Due to this fact, cell suspension of L. meyenii represent a generous advantage on CS production.…”
Section: Substrate/elicitormentioning
confidence: 87%